Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.18632/aging.202985
|View full text |Cite
|
Sign up to set email alerts
|

Strong association between the dietary inflammatory index(DII) and breast cancer: a systematic review and meta-analysis

Abstract: The association between the Dietary Inflammatory Index (DII) and breast cancer risk has been widely reported in recent years, but there is still controversy about whether a pro-inflammatory diet is a risk factor for breast cancer. We conducted a meta-analysis to investigate the relationship between the DII and breast cancer risk in pre-menopausal and post-menopausal women. We comprehensively searched PubMed, Embase and the Cochrane Library in January 2021 to identify articles reporting an association between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In recent years, the associations between DII and sitespecific cancers have been reported (14)(15)(16)(17)36). Hua et al and Zhu et al conducted two systematic reviews and dose-response meta-analyses on DII and upper aerodigestive tract cancer (UADT) (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the associations between DII and sitespecific cancers have been reported (14)(15)(16)(17)36). Hua et al and Zhu et al conducted two systematic reviews and dose-response meta-analyses on DII and upper aerodigestive tract cancer (UADT) (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the associations between DII and site-specific cancers have been reported ( 14 17 , 36 ). Hua et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as indicated in a recent meta-analysis, several studies have produced null results for the DII in association with BrCA. 56 Previous studies have shown that adherence to healthy dietary patterns such as the Healthy Eating Index, 57 the Dietary Approach to Stop Hypertension, 58 and the Mediterranean Diet 59 are associated with a decreased risk of BrCA. Higher scores based on these indices, which are consistently inversely related to the DII/E-DII, indicate more anti-inflammatory diets.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, large case‐control studies in Italian 30 and Chinese women 31 have shown that the DII is positively associated with the risk of BrCA. Nevertheless, as indicated in a recent meta‐analysis, several studies have produced null results for the DII in association with BrCA 56 . Previous studies have shown that adherence to healthy dietary patterns such as the Healthy Eating Index, 57 the Dietary Approach to Stop Hypertension, 58 and the Mediterranean Diet 59 are associated with a decreased risk of BrCA.…”
Section: Discussionmentioning
confidence: 99%